Liquid Force and Rupture Distance between Two Particles - Cheng Pu; Fengyin Liu; Shaohan Wang (Advances in Materials Science and Engineering)
The study of liquid force has a special meaning to industrial manufacturing. By taking the liquid bridges between equal and unequal particles as objects, the liquid force-displacement curves were measured and recorded by using a novel Nano UTM T150 tensile system. The influences of diameter, diameter ratio, liquid volume, and the surface tension on the liquid force-distance curve, the maximum liquid force, and rupture distance were compared and sorted. The results show that the maximum liquid force and rupture distance both increase with the increase in liquid volume, particle diameter, diameter ratio, and surface tension. The diameter plays a decisive role in determining the value of the maximum liquid force compared with surface tension and liquid volume, which only influence the force value in a local range. The rupture distance shows a positive correlation with liquid volume and surface tension and a negative correlation with the diameter or diameter ratio. The maximum liquid force between unequal particles is about half of the sum of the force between the equal spheres of larger and smaller size in that system.